Consumers' Perception of Omah Maha Hampers of College Students' Entrepreneurship - Amalia, Puji Astuti; Syam, Herdi; Maulita; Yahya, Shanty; Karim, Syafei (Indonesian Journal of Business and Entrepreneurship, 2023)
This research is a qualitative study with a case study approach. This research was conducted in one Micro, Small and Medium Enterprise, Omah Maha. Omah Maha is a Micro, Small and Medium Enterprise organized by a group of students supported by Politeknik Negeri Samarinda. This research aimed to know consumers' perceptions of the hamper Omah Maha produced. The hamper created by Omah Maha is unique since it is a new business supported by Politeknik Negeri Samarinda, yet it is well known. Moreover, it has produced more than 50 packages in the first month. The research was conducted from September to November 2022. The data were collected through questionnaires, interviews and documentation. The subjects of the study were the consumers who met the criteria of this study. The data were analyzed and described qualitatively. The study found that the consumers had some perceptions of the hamper produced by Omah Maha, such as the price being affordable since the consumers could decide the price range. Furthermore, the strategy of promotion was interesting. Omah Maha used some digital platforms to advertise their product and offer special prices in the advertisement. The consumers also thought that the hamper had cultural value. Moreover, social factors, location and excellent service are also some factors that were considered. Keywords: consumers' perceptions, hamper, cultural value, Omah Maha, case study